2020
DOI: 10.21511/ppm.18(1).2020.05
|View full text |Cite
|
Sign up to set email alerts
|

Scrambling for higher metrics in the Journal Impact Factor bubble period: a real-world problem in science management and its implications

Abstract: Universities and funders in many countries have been using Journal Impact Factor (JIF) as an indicator for research and grant assessment despite its controversial nature as a statistical representation of scientific quality. This study investigates how the changes of JIF over the years can affect its role in research evaluation and science management by using JIF data from annual Journal Citation Reports (JCR) to illustrate the changes. The descriptive statistics find out an increase in the median JIF for the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…However, empirical evidence has pointed out that the current system is a major reason for researchers engaging in questionable research practices (QRPs) (Bonn & Pinxten, 2019). The 'publish or perish' culture (Vuong, 2019) or the abuse of journal metrics (Tran et al, 2020) has been held widely accountable. Sacco et al (2018) suggested that believing QRPs is necessary for career advancement is correlated with higher acceptance of QRPs.…”
Section: Improving the Transparency Of Rns: Causes And Solutionsmentioning
confidence: 99%
“…However, empirical evidence has pointed out that the current system is a major reason for researchers engaging in questionable research practices (QRPs) (Bonn & Pinxten, 2019). The 'publish or perish' culture (Vuong, 2019) or the abuse of journal metrics (Tran et al, 2020) has been held widely accountable. Sacco et al (2018) suggested that believing QRPs is necessary for career advancement is correlated with higher acceptance of QRPs.…”
Section: Improving the Transparency Of Rns: Causes And Solutionsmentioning
confidence: 99%
“…However, regardless of the pure intention, using a mere number to rank a journal has many shortcomings and can be abused in various ways (Tran et al, 2020b, Berenbaum, 2019. Thus, in their reports, Web of Science has to use more sophisticated methods to provide an overview of the scientific development in South and East Asia (Adams et al, 2019), or to identify hot topics and new research fronts (Szomszor et al, 2020).…”
Section: Bibliometricsmentioning
confidence: 99%
“…Therefore, it is extremely necessary to propose a criteria and measures for domestic scientific journals to access international publishing standards as well as improve the capacity of Vietnamese researchers. In a number of studies related to improving the quality of international publications of scientists in Vietnam, the issue of improving the capacity of ranking research journals appeared in the works of Chung et al(2019), Cuong, Loc, Trung, & Trung (2020), Ho et al (2019) Hoang et al (2020), Hung (2016), Nguyen et al (2020), Trang et al (2020), Trung, Linh, Phuong, Toan, & Hoang (2020). Most authors have confirmed the trend of increasing the quantity and quality of research in general and research in the field of educational science in Vietnam.…”
Section: Introductionmentioning
confidence: 98%